2002
DOI: 10.1111/j.1572-0241.2002.05835.x
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide Cir Capsules (Once Or Twice Daily Divided-Dose) in Active Crohn's Disease: A Randomized Placebo-Controlled Study in The United States

Abstract: Treatment of symptomatic Crohn's disease with budesonide CIR capsules (9 mg daily) was safe, and remission rates were similar to those achieved in previous trials. Although the remission rate did not significantly differ from the placebo response in this study, there was a significant change in the mean CDAI from baseline in the combined treatment groups relative to the placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(34 citation statements)
references
References 12 publications
1
30
0
3
Order By: Relevance
“…Two randomized, double-blind, placebo-controlled studies investigated the treatment of flare in patients with mild-to-moderate active Crohn's disease of the ileum or ascending colon, and showed that controlled-ileal-release budesonide capsules were more effective than placebo for induction of remission (Table 1) [Greenberg et al 1994;Tremaine et al 2002]. A controlled-ileal-release formulation of budesonide more effectively induced remission than a slow-release formulation of mesalamine in patients with active Crohn's disease [Thomsen et al 1998].…”
Section: Efficacy In Crohn's Diseasementioning
confidence: 99%
“…Two randomized, double-blind, placebo-controlled studies investigated the treatment of flare in patients with mild-to-moderate active Crohn's disease of the ileum or ascending colon, and showed that controlled-ileal-release budesonide capsules were more effective than placebo for induction of remission (Table 1) [Greenberg et al 1994;Tremaine et al 2002]. A controlled-ileal-release formulation of budesonide more effectively induced remission than a slow-release formulation of mesalamine in patients with active Crohn's disease [Thomsen et al 1998].…”
Section: Efficacy In Crohn's Diseasementioning
confidence: 99%
“…Well controlled studies have revealed that budesonide is significantly more effective than placebo and 5-ASA, and is about as effective as conventional corticosteroids for inducing remission in active CD. [92][93][94] Therefore, budesonide has been recommended as a first-line therapy for mild to moderate CD of the ileum and proximal colon in an American Gastroenterological Association position statement and in the European Crohn's and Colitis Organization Consensus. 95,96 For those patients who do not respond to the first-line therapy described above and for those with moderate to severe CD, oral prednisone 40-60 mg/day should be given.…”
Section: Medical Management 1) Induction Of Remissionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Validity (comparison of a new index against a reference measure), reliability (test of consistency of the index when readministered under similar conditions at two separate intervals), and responsiveness (ability of the index to measure clinically important change over time) of the short CDAI were also evaluated in these nine studies. 13 The protocols for the nine studies were approved by the Institutional Review Boards at each of the participating centers and all patients gave written informed consent.…”
Section: Included Patients and Trialsmentioning
confidence: 99%